SELF-MEDICATION PRACTICES AMONG 1st- AND 2nd-YEAR MEDICAL UNDERGRADUATES - PRABHAKARAN, SONISH S; Prabha MP, Sneha; S, ASHA; Palappallil, Dhanya Sasidharan (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The objectives of our study were to estimate the prevalence of self-medication, to assess the knowledge, attitude, and practice of self-medication, and to compare the risk factors of self-medication practices among 1st-and 2nd-year medical undergraduates, of a Government Medical College in Kerala, India. Methods: A questionnaire-based cross-sectional study was conducted among medical students after obtaining Institutional Ethics Committee approval and informed consent. A pre-validated questionnaire was used to collect data. Descriptive and analytical statistics were performed and variables associated with self-medication were entered into a multivariate logistic regression model to compute adjusted odds ratio (OR) and 95% confidence intervals (95% CI). Results: The response rate was 59.47% (233/375). More than three-quarters of the participants responded correctly to the query on definition of over-the counter drug. As compared to 46.8% of 1st years, 67.6% of 2nd years had practiced self-medication in the past 6 months. The most common medical condition/symptom for consuming self-medication was for managing the common cold and paracetamol was the most common medication. The risk of developing adverse drug reactions was considered a serious threat after self-medication by around three-quarters of the participants. There was a significant association of self-medication practice among the 2nd years as compared to the 1st years (p=0.009, OR-1.64 (95% CI 1.16–2.31). Conclusion: The prevalence of self-medication was high among medical students and there was a greater risk of self-medication among the 2nd years (1.64 times) as compared to the 1st-year students. The study revealed that the students exhibited inadequate knowledge regarding appropriate self-medication. Although they had a positive attitude toward self-medication they commonly engaged in inadequate self-medication practices. Knowledge of medicines obtained for similar previous illnesses and the feeling that there is no need to consult a doctor for minor ailments that were the main reasons for self-medication.